The optimal treatment of invasive ductal and lobular carcinoma occurring at the same time needs to be established - Supriya Peshin; Rafi Iftekher; Rabia Iqbal; Shagun Singh; Moka Nagaishwarya (European Journal of Case Reports in Internal Medicine)
Bilateral breast cancer with distinct histological subtypes poses a significant clinical challenge, requiring an individualised approach to management. This case discusses a 61-year-old postmenopausal woman with concurrent invasive ductal carcinoma (IDC) in the right breast and invasive lobular carcinoma (ILC) in the left breast. IDC, the most common breast cancer subtype, is known for its aggressive behaviour, nodal involvement and metastatic potential, while ILC, representing a smaller percentage of breast cancers, often exhibits an indolent course with diffuse growth patterns. Both tumours in this patient were hormone receptor-positive (ER/PR-positive) and HER2-negative, warranting targeted endocrine therapies. The complexity of this case was further heightened by a significant family history of breast and colon cancers, and comorbid conditions including borderline diabetes, hypertension and coronary artery disease (CAD), which required careful therapeutic consideration to balance efficacy and tolerability. Pathological evaluation confirmed stage II, grade 2 IDC in the right breast with one positive sentinel lymph node and stage I, grade 1 ILC in the left breast with no nodal involvement. Given her extensive family history, the patient opted for bilateral mastectomy with sentinel lymph node biopsy. Multidisciplinary tumour board discussions emphasised the integration of genetic testing, including BRCA1/2 evaluation, and Oncotype DX genomic profiling to assess recurrence risk and guide adjuvant chemotherapy decisions. Recommendations included adjuvant radiation therapy for the right breast, endocrine therapy for both tumours and the incorporation of CDK 4/6 inhibitors based on recent evidence from the NATALEE trial, which demonstrated improved outcomes in high-risk, hormone receptor-positive, HER2-negative breast cancers. The case highlights the need for further research into the optimal treatment strategies for synchronous breast cancers, a potential knowledge gap in current oncology practice. A literature review revealed limited reports addressing similar cases, underscoring the lack of consensus guidelines. Our approach integrates the best available evidence with multidisciplinary expertise to inform a personalised treatment plan. The learning points emphasise the need for establishing evidence-based strategies for managing synchronous bilateral breast cancers.